2022
DOI: 10.3352/jeehp.2022.19.37
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ satisfaction level with e-learning during the COVID-19 pandemic and its related factors: a systematic review

Abstract: Purpose: This review investigated medical students’ satisfaction level with e-learning during the coronavirus disease 2019 (COVID-19) pandemic and its related factors.Methods: A comprehensive systematic search was performed of international literature databases, including Scopus, PubMed, Web of Science, and Persian databases such as Iranmedex and Scientific Information Database using keywords extracted from Medical Subject Headings such as “Distance learning,” “Distance education,” “Online learning,” “Online e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The COVID-19 pandemic accelerated this transformation, triggering an urgent global shift from traditional face-to-face (FTF) teaching to virtual remote learning in academic institutions. This emergency transition has brought about unique challenges in course delivery, including adapting traditional teaching methods for effective online instruction, struggles to keep students engaged and motivated, and preserving sufficient social interaction among learners and instructors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic accelerated this transformation, triggering an urgent global shift from traditional face-to-face (FTF) teaching to virtual remote learning in academic institutions. This emergency transition has brought about unique challenges in course delivery, including adapting traditional teaching methods for effective online instruction, struggles to keep students engaged and motivated, and preserving sufficient social interaction among learners and instructors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this result, the literature has shown the direct effect of students’ computer or internet self-efficacy on course satisfaction [ 25 – 27 ]. A systematic review showed that students' previous online learning experience and being familiar with the system increased their satisfaction level [ 28 ]. Similarly, another study found that previous positive experience with the learning platform and students’ level of digital competency has a positive effect on educational satisfaction [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another post-COVID-19 study of 64 medical students at a United States-based allopathic medical school that moved the entire pre-clinical curriculum to a virtual format during the pandemic demonstrated that 70.3% of students reported an unchanged or improved overall medical education in a virtual course module compared to a previous module that was taught in a traditional face-to-face setting [ 25 ]. Furthermore, a recent systematic review of 24 studies measuring medical student satisfaction with e-learning during the pandemic indicated that 51.8% of the 15,473 medical students studied were satisfied [ 26 ].…”
Section: Discussionmentioning
confidence: 99%